A Study on the Female Chest Contour with Elliptic Fourier Analysis (Journal of Fiber Bioengineering and Informatics, 2018)
Elliptic Fourier Analysis (EFA) is an important tool in shape reconstruction. To get the best female subject fitting result, we took the following processes. Firstly, three kinds of sampling methods were taken, including curvature sampling, random sampling and equally spaced sampling. According to our experiment result, equally spaced had the best performance. Secondly, eclectic sampling density was decided by the mean distance and conference. Finally, the number of harmonics used by EFA was decided by the experimental error requirement. The experimental results indicate that the EFA was an powerful and efficient approach in chest shape fitting.
Keywords: Elliptic Fourier Analysis; Sampling Method; Sampling Points; Harmonics.